Negotiating Identities: Growing Up Female, Jewish and Mexican. Issue 3 (15th March 2016) - Avendaño, Nadia
Abstract: The prominent Sephardic-Mexican author Rosa Nissán explores her relationship to both her Sephardic Jewish identity as well as to her Mexican identity in the semi-autobiographical novels Novia que te vea (1992) and Hisho que te nazca (1996) via her protagonist Oshinica. Nissán redefines the Mexican literary canon by offering new perspectives about Mexican society and culture from a feminist Jewish perspective. The author also counters the greater Mexican hegemony by revealing a subculture of Mexican life and debunking the myth of a mestizo nation as a single and unified family. Nissán argues for a more inclusive identity by opening a space to experience both cultures, forging aspects of both the Jewish and the Mexican cultures into a singular one, thus affirming a pluralistic identity.